China's economy a collection of surveys - Claus, Iris; Oxley, Les (West Sussex, UK Wiley-Blackwell, 2015)
"This collection of critical surveys provides readers with a range of up-to-date work from leading scholars in the area, writing on some of the key issues facing China, as they survey the present and future challenges of the Chinese economy Nine papers provide detailed discussion on key aspects of the past, present and future of the Chinese economy Leaders in their relevant fields of scholarship tackle some of the critical issues facing China Contributors identify common themes, including the household registration system, urbanization, demographic transition, inequality and the sustainability of economic growth Articles provide a critical review of the literature and discuss policy implications and areas for future research "-- Provided by publisher.
"Explores topics including the household registration system, urbanization, demographic transition, inequality, and the sustainability of economic growth"--Provided by publisher.
Machine generated contents note: 1. The Chinese Economy, Past, Present and Future Iris Claus and Les Oxley 2. A Survey of Recent Research in Chinese Economic History Kent Deng 3. Demographic Transition and Labour Market Changes: Implications for Economic Development in China Yang Du and Cuifen Yang 4. Pension Reform in China: Challenges and Opportunities Yong Cai and Yuan Cheng 5. The Evolution of the Housing Market and its Socioeconomic Impacts in the Post-Reform People's Republic of China: A Survey of the Literature Jie Chen and Xuehui Han 6. Urbanization and Urban Systems in the People's Republic of China: Research Findings and Policy Recommendations Ming Lu and Guanghua Wan 7. Income Inequality in the People's Republic of China: Trends, Determinants, and Proposed Remedies Chen Wang, Guanghua Wan and Dan Yang 8. The Evolving Geography of China's Industrial Production: Implications for Pollution Dynamics and Urban Quality of Life Siqi Zheng, Cong Sun, Ye Qi and Matthew E. Kahn 9. Innovation in China Peilei Fan 10. China's Service Trade Hejing Chen and John Whalley Index.
Includes bibliographical references and index.
Keywords: China -- Economic conditions -- 2000-.; China -- Economic policy -- 2000-.; China -- Social conditions -- 2000-.